E-Learning On Students’ Academic Success During Covid-19: With Special Reference To Management Undergraduates Of Non-State Universities - Hirushan Saveen Weerasinghe; Petro Biyanwila; Serani Bogahage; Shehan Thiwanka; Ranitha Weerarathna; Geethma Pathirana (International Journal of Evaluation and Research in Education (IJERE), 2022)
Due to the recent outbreak of the COVID-19 pandemic, Sri Lankan educational institutes were forced to transform to e-learning. Hence, the purpose of this study is to examine the effect of E-learning on Academic success with special reference to the management undergraduates of non-state universities of Sri Lanka. This study is a quantitative research study and based on a deductive research approach. For data collection, researchers used a questionnaire based on a convenience sampling method. A sample of 332 students was considered, including 3rd and 4th year management undergraduates from two non-state universities. The overall reliability was reported to be 0.944 (Cronbach's alpha). The finding revealed that having e-learning as the major independent variable has a significant positive impact on academic success in the regression model. Further, it also revealed a strong correlation of.872. Moreover, The results represented a positive moderating effect on student satisfaction between e-learning and academic success. The findings of this study can serve as a guideline for higher educational institutions in focusing on the major factors influencing e-learning on academic success and developing appropriate initiatives to enhance the modern e-learning process. It can be further emphasized that academic success is moderated by student satisfaction.